Evaluating the Insomnia Severity Index among South African first responders: evidence from classical test theory, Rasch, and Mokken analyses - Pretorius, Tyrone B.; Padmanabhanunni, Anita (Frontiers in Sleep, 2025)
BackgroundSleep is essential for physical health and psychological wellbeing, and insomnia is strongly associated with mental health difficulties, including depression, anxiety, and fatigue. Among first responders, the prevalence of insomnia is particularly high due to chronic exposure to stress, trauma, and irregular work hours.AimAs part of a broader study focusing on the mental health of first responders in South Africa, the current study examined the psychometric properties of the Insomnia Severity Index from three different psychometric perspectives: classical test theory, Rasch analysis and Mokken scale analysis.MethodsParticipants were first responders (n = 429) in the Western Cape province of South Africa and they included police officers (n = 309) and paramedics (n = 120). They completed the Insomnia Severity Index (ISI), the Patient Health Questionnaire-9, the Generalized Anxiety Disorder-7, and the Chalder Fatigue Questionnaire.ResultsThe three psychometric paradigms converged to confirm that the ISI measures a unidimensional scale. Furthermore, all three paradigms provided evidence for the construct validity of the ISI. In addition, classical test theory indices provided evidence for convergent and discriminant validity. Lastly, the correlations between insomnia as measured by the ISI and depression, anxiety, and fatigue provided evidence for concurrent validity.ConclusionThese findings affirm that the ISI is a stable and sound tool for assessing insomnia severity within the first responder population. The absence of measurement bias across gender and professional roles also enhances the practical utility of the ISI, as it ensures equitable assessment across subgroups within the first responder workforce. The ISI emerges from this study as a valuable resource for clinicians, researchers, and occupational health professionals working with South African first responders.